IMPLEMENTASI PROGRAM SEKOLAH SEHAT DALAM MENUMBUHKAN PERILAKU HIDUP BERSIH DAN SEHAT - Khayatuti, Nur; Azainil, Azainil; Mulawarman, Widyatmike Gede; Yudo, Yudo (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2024)
Healty and intelligent generation became capital for development this study focuses on describing the implementation of healthy school programs in developing clean and healthy living behaviors in public elementary schools in Bontang City. The method in this study uses a qualitative approach. Data collection techniques use observation, interviews and documentation. Data analysis techniques use data collection, data reduction and data presentation.The results show: (1) Planning a healthy school program begins with the socialization of the program with a meeting and produce activity program plans (2) The Implementation of a nutritious healthy school program is the activities to eat together with balanced nutritional provisions, healthy physical gymnastics, healthy walks, stretching during class time, healthy immunization, first to fourth grade students and dental immunization for first grade students. Clean and healthy living behavior is habituation to maintain personal hygiene and the environment (3) Supervision of healthy school programs is carried out during eating together, gymnastics and immunization activities during implementation. (4) Supporting factors and inhibiting factors for healthy nutrition, physical health, healthy immunization supporting factors of human resources and, infrastructure facilities owned by schools. Inhibiting factors for healthy nutrition: there are still students who forget to keep healthy in rains, and healthy immunization, students who refuse clean and healthy living behavior. There are students who are not accustomed to disposing of garbage according to its type. In the implementation of this healthy school program, it is generally well implemented and some require further habituation.